Observation of strong nuclear suppression in exclusive 𝐽/𝜓 photoproduction in Au+Au ultraperipheral collisions at RHIC - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physical review letters, 2024)
We report a measurement of exclusive 𝐽/𝜓 and 𝜓⁡(2⁢𝑠) photoproduction in Au+Au ultraperipheral collisions at √𝑠NN=200 GeV using the STAR detector. For the first time, (i) the 𝜓⁡(2⁢𝑠) photoproduction in midrapidity at the Relativistic Heavy-Ion Collider has been experimentally measured; (ii) nuclear suppression factors are measured for both the coherent and incoherent 𝐽/𝜓 production. At average photon-nucleon center-of-mass energy of 25.0 GeV, the coherent and incoherent 𝐽/𝜓 cross sections of Au nuclei are found to be 71 ±10% and 36 ±7%, respectively, of that of free protons. The stronger suppression observed in the incoherent production provides a new experimental handle to study the initial-state parton density in heavy nuclei. Data are compared with theoretical models quantitatively.